The impact of meta-cognition instruction on perfectionism and the life quality of high school students - Hayati, Mozhgan; Parto, Afsaneh (Revista Gestão & Tecnologia, 2018)
This study aimed to find out the impact of meta-cognition teaching on perfectionism and the quality of high school students` lives. The study used quasi-experimental method, pre-test, and post-test with a control group. The population of the study included all the high school students in Larestan city during 1396-1397 (2017-2018) academic year. Using convenient sampling method, 30 students were chosen from among the population available, then this sample was divided into two groups of 15 with one being an experimental and the other being the control group. Hill`s Perfectionism Questionnaire and Life Quality Questionnaire (SF-36) and single-variable co-variance data analysis and SPSS version 22 were used in the study in order to analyze the data. The results of the study indicated a significant difference between the experimental and control group in terms of the scores obtained from Perfectionism (P<0.0001, F=44.20) and Life Quality (P<0.0001, F=30.70). It can be concluded that meta-cognition therapy can be effective in lowering the degree of perfectionism and raising the quality of high school students` lives.